Cultural theory and popular culture : an introduction - Storey, John (Routledge, 2018)
Cultural Theory and Popular Culture: An Introduction, sixth edition, has been extensively revised throughout. As before, the book presents a clear and critical survey of competing theories of and various approaches to popular culture. Its breadth and theoretical unity, exemplified through popular culture, means that it can be flexibly and relevantly applied across a number of disciplines. Also retaining the accessible approach of previous editions, and using appropriate examples from the texts and practices of popular culture, this new edition remains a key introduction to the area.